Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0640
|View full text |Cite
|
Sign up to set email alerts
|

Forbidden Fruit: Dominance Relationships and the Control of Shoot Architecture

Abstract: Plants continually integrate environmental information to make decisions about their development. Correlative controls, in which one part of the plant regulates the growth of another, form an important class of regulatory mechanism, but their study has been neglected and their molecular basis remains unclear. In this review, we examine the role of negative correlative controls or 'dominance' phenomena in the regulation of shoot architecture. Apical dominance, in which actively growing shoot branches inhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 116 publications
(177 reference statements)
2
37
0
Order By: Relevance
“…Consistent with previous suggestions, we propose that a conserved core pathway could underlie all primigenic dominance phenomena (Bangerth, ; Walker and Bennett, in press), including fruit morph determination in Aethionema species. In this basic regulatory module, high auxin export from developing organs leads to their growth and dominance in the shoot system and conversely low auxin export leads to inhibition (Bangerth, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous suggestions, we propose that a conserved core pathway could underlie all primigenic dominance phenomena (Bangerth, ; Walker and Bennett, in press), including fruit morph determination in Aethionema species. In this basic regulatory module, high auxin export from developing organs leads to their growth and dominance in the shoot system and conversely low auxin export leads to inhibition (Bangerth, ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, at a mechanistic level, carpic dominance is not well characterized in any species. Nevertheless, we can offer some speculation, based on evidence derived from measuring hormone and gene expression levels (Figures and S6) and on the assumption that the regulatory network controlling carpic dominance is closely related to the shoot branching regulatory network (Walker and Bennett, in press). This hypothesis has been previously proposed because of striking similarities between these phenomena in terms of auxin action and transport (Bangerth, ) and is further supported by the fact that both processes react in similar ways to environmental factors (Bangerth, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that end-of-flowering involves gene expression changes at the floral meristem which are at least in part controlled by the FRUITFULL-APETELA2 pathway [3,4], however there is limited understanding of how this process is controlled and the communication needed at the whole plant level. Here, we provide new information providing a framework for the fruit-to-meristem (F-M) communication implied by the GPA model [5]. We show that floral arrest in Arabidopsis is not 'global' and does not occur synchronously between branches, but rather that the arrest of each inflorescence is a local process, driven by auxin export from fruit proximal to the inflorescence meristem (IM).…”
mentioning
confidence: 92%
“…While it is certainly true that plant growth can be absolutely limited by lack of resources, it is also the case that plants can pro-actively 'choose' not to invest in more growth. Indeed, where sufficient information is present in the environment to allow plants to predict future resource scarcity, it is a far more useful strategy to pro-actively limit growth to avoid resource limitations, than to grow until resources are exhausted (Walker & Bennett, 2018). We can characterise changes in plant development as 'decisions' if they are taken in the absence of resource limitations, and 'responses' if they occur due to resource limitations.…”
Section: Introductionmentioning
confidence: 99%